Design and Implementation of a Smart Contract-Based Consent Management Model for Secure Personal Data Sharing - Mandinyenya, Godwin; Malele, Vusumuzi (PT. SNN MEDIA TECH PRESS, 2025)
Emerging data-sharing paradigms demand robust mechanisms to ensure user consent is dynamically managed while preserving data sovereignty. This paper proposes a blockchain-driven consent management model that leverages smart contracts, offline storage, and a JavaScript/JSON front end to empower data owners in healthcare, finance, and identity management. The framework decentralizes consent logging, automates access enforcement, and integrates GDPR-compliant